Recommendations regarding cardiac stereotactic body radiotherapy for treatment refractory ventricular tachycardia - Krug, David; Blanck, Oliver; Andratschke, Nicolaus; Guckenberger, Matthias; Jumeau, Raphael; Mehrhof, Felix; Boda-Heggemann, Judit; Seidensaal, Katharina; Dunst, Jürgen; Pruvot, Etienne; Scholz, Eberhard P.; Saguner, Ardan M.; et al. (Heart rhythm, 2021)
Background - Ventricular tachycardia (VT) is a potentially lethal complication of structural heart disease. Despite optimal management, a subgroup of patients continue to suffer from recurrent VT. Recently, cardiac stereotactic body radiotherapy (CSBRT) has been introduced as a treatment option in patients with VT refractory to antiarrhythmic drugs and catheter ablation. - Objective - The purpose of this study was to establish an expert consensus regarding the conduct and use of CSBRT for refractory VT. - Methods - We conducted a modified Delphi process. Thirteen experts from institutions from Germany and Switzerland participated in the modified Delphi process. Statements regarding the following topics were generated: treatment setting, institutional expertise and technical requirements, patient selection, target volume definition, and monitoring during and after CSBRT. Agreement was rated on a 5-point Likert scale. The strength of agreement was classified as strong agreement (≥80%), moderate agreement (≥66%) or no agreement (<66%). - Results - There was strong agreement regarding the experimental status of the procedure and the preference for treatment in clinical trials. CSBRT should be conducted at specialized centers with a strong expertise in the management of patients with ventricular arrhythmias and in stereotactic body radiotherapy for moving targets. CSBRT should be restricted to patients with refractory VT with optimal antiarrhythmic medication who underwent prior catheter ablation or have contraindications. Target volume delineation for CSBRT is complex. Therefore, interdisciplinary processes that should include cardiology/electrophysiology and radiation oncology as well as medical physics, radiology, and nuclear medicine are needed. Optimal follow-up is required. - Conclusion - Prospective trials and pooled registries are needed to gain further insight into this promising treatment option for patients with refractory VT.